Dampak E-Tax System dan Konsultan Pajak Terhadap Kepatuhan dengan Kepuasan Wajib Pajak Sebagai Variabel Intervening - Kribiyantara, Yohanes; Dura, Justita; Bukhori, Mohammad (Politeknik Ganesha Medan, 2024)
Because tax revenue is the main source of state funding for national development, it is essential for the government, particularly the Directorate General of Taxes, to improve taxpayer compliance with tax obligations. Shifting from traditional face-to-face services to digital services, known as the electronic tax system (e-tax system), includes online reporting through e-filing, e-form, e-bupot unification, e-bupot21, and e-invoice. This is one strategy to improve compliance. Tidak banyak penelitian yang dilakukan tentang dampak dari these services on tax compliance, mediated by taxpayer satisfaction, meskipun mereka dimaksudkan untuk mempersederhanakan pembayaran pajak dan diwajibkan. A sample of 117 taxpayers, who are clients of tax consultants and members of the Indonesian Tax Consultants Association (IKPI) Balikpapan Branch, was used in this study to investigate the impact of the e-tax system on taxpayer compliance in Balikpapan City, with taxpayer satisfaction as an intervening variable. SmartPLS 4.0.9.6 software was used for data analysis using SEM-PLS. Hasilnya menunjukkan bahwa penerapan e-tax system berdampak positif dan signifikan terhadap taxpayer satisfaction dan compliance. Furthermore, taxpayer satisfaction has a positive and significant impact on taxpayer compliance. Additionally, as an intervening variable, taxpayer satisfaction has a positive and significant impact on taxpayer compliance